Pengukuran Kinerja Rantai Pasok Pada Industri Karet Remah dengan Pendekatan SCOR (Supply Chain Operations Reference) - Harma, Beni; Adelino, Muhammad Ilham; Ramadayanti, Miza; Triha, Hadigufri (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2024)
One of the pivotal aspects of a company lies in its supply chain. The company must effectively and efficiently manage their supply chains to support production quality, achieve organizational goals, and ensure customer satisfaction. This research aims to determine the key performance indicators (KPIs) for the crumb rubber processing industry and provide suggestions for improving its supply chain performance. Supply chain performance measurement was conducted using the Supply Chain Operations Reference (SCOR) model in conjunction with the Analytical Hierarchy Process (AHP) method to determine the weights of the KPIs. The research found that the overall supply chain performance score for the crumb rubber company was 84.92, categorizing it as "Good." However, among the 26 Key Performance Indicators (KPIs) identified, three indicators (i.e. production of defective products, consumer complaints, and returns of defective products) fell into the "Poor" category. Hence, it is crucial for crumb rubber industry stakeholders to address these three criteria to enhance supply chain performance.